2008
DOI: 10.2533/chimia.2008.383
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Malformations in Whitefish from Lake Thun: Defining the Case and Evaluating the Role of EDCs

Abstract: The objectives of this project were to evaluate i) whether the gonad alterations of whitefish ( Coregonus lavaretus spp.) in Lake Thun represent abnormal morphological variations specific to this lake, and, if so, ii) whether the malformations are related to chemical exposure, in particular to exposure to endocrine-disrupting compounds (EDCs). Large-scale monitoring data revealed that, although whitefish in other lakes display some background variation of gonad morphology, the situation in Lake Thun, is unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…3d). It is noteworthy that the percentage of pike in which gonad alterations were found is similar (~30%) to that observed for the whitefish population in Lake Thun (Bernet et al 2004(Bernet et al , 2008. Interestingly, a detailed investigation of male pike gonads from the 2 lakes studied (n = 27 from Mosa g and n = 32 from Klebarskie) showed no alterations in the testis (J.…”
Section: Discussionsupporting
confidence: 67%
“…3d). It is noteworthy that the percentage of pike in which gonad alterations were found is similar (~30%) to that observed for the whitefish population in Lake Thun (Bernet et al 2004(Bernet et al , 2008. Interestingly, a detailed investigation of male pike gonads from the 2 lakes studied (n = 27 from Mosa g and n = 32 from Klebarskie) showed no alterations in the testis (J.…”
Section: Discussionsupporting
confidence: 67%
“…The gonad abnormalities observed in the Baltic herring resemble those of the European whitefish (Coregonus lavaretus) from Lake Thun, Switzerland, which also showed a high variety of morphological types (Bernet et al 2004(Bernet et al , 2008. The two species shared some similarities in the gross morphology of gonads, but there were also differences between them.…”
Section: The Types Of Gonad Malformationsmentioning
confidence: 75%
“…However, they may also remain unnoticed, if for instance the sexual maturity is determined without taking the entire gonad out so that its morphology can be seen properly. Beside the lake whitefish (Bernet et al 2004(Bernet et al , 2008, gonad anomalies have been found also in some tropical fish (Omotosho 1987), and especially frogs and reptiles suffer from this condition (e.g., Guillette et al 2000;Hecker et al 2006). In many cases, the anomalies are causally linked with the chronic exposure to herbicides (Coady et al 2005) or other environmental contaminants disturbing the endocrine system of an animal.…”
Section: Possible Causes Of Gonad Malformationsmentioning
confidence: 99%
“…data). Second, mRNA VTG levels of male whitefish from both experimental groups were not increased compared with mRNA VTG levels of wild male whitefish from Lake Thun (sampling at 4 different sites, medians = 0.33 to 9.68 copies VTG mRNA 1000 -1 copies 18s-RNA; Bernet et al 2008). Third, Kipfer at al.…”
Section: Discussionmentioning
confidence: 99%